Musa germplasm A and B genomic composition differentially affects their susceptibility to banana bunchy top virus and its aphid vector, Pentalonia nigronervosa - Ngatat, S.; Hanna, R.; Lienou, J.; Ghogomu, R.; Nguidang, S.P.K.; Enoh, A.C.; Ndemba, B.; Korie, S.; Fotso Kuate, A.; Nanga, S.N.; Fiaboe, K.; Kumar, P. Lava (MDPI, 2022)
Banana bunchy top disease (BBTD), caused by the banana bunchy top virus (BBTV, genus Babuvirus), is the most destructive viral disease of banana and plantain (Musa spp.). The virus is transmitted persistently by the banana aphid, Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae). While research efforts have focused on screening Musa genotypes for BBTD resistance, comparatively little work has been carried out to identify resistance to banana aphids. This study assessed 44 Musa germplasm of different A and B genome composition for the performance of banana aphids under semicontrolled environmental screenhouse conditions and in a field trial established in a BBTD endemic location. In the screenhouse, the AA diploid Calcutta 4 had the lowest apterous aphid density per plant (9.7 ± 4.6) compared with AAB triploid Waema, which had the highest aphid densities (395.6 ± 20.8). In the field, the highest apterous aphid density per plant (29.2 ± 6.7) occurred on the AAB triploid Batard and the lowest (0.4 ± 0.2) on the AA diploid Pisang Tongat. The AA diploid Tapo was highly susceptible to BBTD (100% infection) compared with the genotypes Balonkawe (ABB), PITA 21 (AAB), Calcutta 4 (AA), and Balbisiana Los Banos (BB), which remained uninfected. The Musa genotypes with apparent resistance to BBTD and least susceptibility to aphid population growth provide options for considering aphid and BBTD resistance in banana and plantain breeding programs.